ANALYZING PERTURBATION EFFECTS ON LOW SATELLITE ORBITAL ELEMENTS AT DIFFERENT TERMS OF EARTH POTENTIAL - Ardhan Y. Omar; Ahmed K. Izzet; Abed T. Jasim (Journal Park Publishing, 2024)
The space technology made it feasible to launch and operate man-made satellites for the purpose of studying the Earth's dimensions and shape from orbit or to examine them as targets from the surface of the world.
Keywords: Earth's Oblateness, Perturbations, Orbital elements, Zonal harmonic, gravitational potential.